REVITALISASI PEMBELAJARAN GEN Z: OPTIMALISASI MEDIA BERBASIS AI PADA MATERI MENULIS ESSAY DI SMP SWASTA DELISHA - Elma, Elma Purba; Adellya Rosari Siregar; Berkatiah; Dwinda Khoyriyah; Diah Pashya Togatorop; Elly Prihasti Wuriyani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effectiveness of Artificial Intelligence (AI)-based learning media in improving students’ essay writing skills at SMP Swasta Delisha. The research employed a quasi-experimental design with a pretest-posttest control group. Data were collected through essay writing tests and student perception questionnaires. The results showed that the experimental group achieved an average score of 94.08, while the control group scored 44.11, with tcount = 14.67 > ttable = 2.048, indicating a significant difference between the two groups. The use of AI media effectively enhanced students’ writing skills, motivation, and engagement. Theoretically, this finding supports Vygotsky’s social constructivist theory, emphasizing technology as scaffolding that fosters independent thinking and writing. Therefore, integrating AI into Indonesian language learning represents an innovative strategy aligned with Generation Z characteristics and supports the Merdeka Curriculum focused on digital literacy.